(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The contemporary world is faced with big challenges and problems: nowadays, in the 21st century, almost one billion humans cannot read, this number is increasing and currently encompasses one sixth of the world ‘s population. This fundamental approach to equality is a starting point to solve problems in education. Education belongs to everyone equally, regardless of one ‘s psychosocial and inclusive needs. Implementation of inclusive education in schools not only provides quality education and integration for person with disabilities, but it will also facilitate social progress, when typical students and their parents start to perceive person with disability as normal. This will create an environment where persons with disability are not victims of even positive discrimination, and different abilities and outlooks are balanced and normalized. This paper highlights the ten steps which would reduce school failure and dropout rates, make society fairer and avoid the large social costs of marginalised adults with few basic skills as well as strategies for inclusive education. Thus, we can conclude is that school choice requires careful management from an equity perspective, particularly to ensure that it does not result in increased differences in the social composition of schools.